Antenna pattern analysis using S‐parameters for strongly coupled dipole arrays. Issue 5 (31st January 2019) - Lee, Kyoungmin M.; Kang, Inwoong; Park, Jaedon; Kim, Moonil
Abstract: An antenna pattern and efficiency estimation procedure for uniform linear dipole arrays with large mutual coupling is presented. The feed currents for each dipole elements are extracted from S ‐parameters with antenna arrays being treated as N‐port circuit networks. The dipole current is assumed to maintain a sinusoidal distribution even in array environments. The estimated patterns for E ‐plane and H ‐plane linear array examples as well as a Yagi‐Uda sample confirm the validity of the proposed procedure.